Analisis Strategi Guru Dalam Meningkatkan Keterampilan Berbicara Siswa Dalam Proses Pembelajaran Kelas IV di SDN 7 Kesu’ - Hendrik Hendrik (LPPM UKI Toraja, 2022)
The purpose of this study was to describe the teacher's strategy in improving students' speaking skills in the fourth grade learning process at SDN 7 Kesu'. This type of research is descriptive qualitative research. The source of this research is the fourth grade teacher at SDN 7 Kesu. Data collection techniques used are observation, interviews, and documentation. Data analysis technique with data reduction stages, data study, and drawing conclusions. The results of the study concluded that strategies that can improve students' speaking skills are by conducting simulation activities (simulation games), storytelling and telling stories, inviting students to play characters in a story, and inviting students to have conversations.